Learning from Mistakes: A Thematic Analysis of Flight 401's Situational Awareness Lapses - Yıldız, Ezgi (Nusantara Journal of Behavioral and Social Science, 2024)
Situational awareness is a fundamental pillar in aviation, essential for safety, operational efficiency, and crew training. This study focuses on the tragedy of Eastern Airlines Flight 401 as a case study to illustrate the importance of effective communication and Crew Resource Management (CRM) in preventing accidents. Through thematic analysis, the research reveals how pilot distractions, cockpit instrument malfunctions, and communication failures in critical conditions contributed to the accident. The findings indicate that comprehensive training that integrally incorporates technological aspects and human factors, as well as an emphasis on effective CRM, is crucial. Practical implications of this research include the development of training modules aimed at enhancing interactive and collaborative communication among crew members. The study also recommends future research focus on aviation technology, air traffic control dynamics, and human-machine interactions, with the goal of deepening understanding of situational awareness dynamics and advancing aviation safety practices. These findings are expected to make a significant contribution to the literature on situational awareness and aviation safety practices.